Writing as Responsive, Situated Practice: The Case for Rhetoric in Canadian Writing Studies - Lukas, Michael; Personn, Tim (Discourse and Writing/Rédactologie, 2019)
This article responds to a widely held presumption that ineffective student writing in Canadian classrooms can be resolved through technical solutions on the model of the popular Grammarly app. In contrast, this article suggests that a solution to the problem of writing instruction should focus on how to teach argument through rhetoric as a responsive, situated practice that occurs within different dynamic discourse communities. The article makes this case by recommending a renewed emphasis on the rhetorical concept of kairos, which provides students with an ethical comportment for decision-making in a pluralistic and uncertain world. This article concludes with a call for revitalized interdisciplinary attention to rhetoric in Canadian writing studies and programs.